The Implementation Of Policies For Structuring And Empowering Street Vendors In Gorontalo City - Anita Dama (Estudiante Law Journal, 2019)
Abstract: The purpose of this study was to find out how the implementation of the policy of structuring and empowering street vendors by the Civil Service Police Unit and to find out what factors influenced the implementation of the policy of structuring and empowering street vendors in Gorontalo City. The type of research used is Empirical Law research, using data types consisting of primary data and secondary data. Data collection techniques were carried out using observation and interview techniques. The results of this study indicate that to improve the economic sector, the Gorontalo City government has issued a policy related to Street Vendors which is packaged in the Gorontalo City Regional Regulation Number 2 of 2017 concerning Structuring and Empowering Street Vendors. The existence of a regulation aims to realize optimal empowerment and governance. Even though the policy has been issued, it cannot be denied that the implementation of the policy will run as it should. This is evidenced by the presence of several street vendors who are still active in locations that should not be occupied. Therefore, in controlling street vendors in the City of Gorontalo, the Civil Service Police Unit uses the legal basis of regional regulations by providing socialization, carrying out control, and implementing arrangements. The factors that influence the effectiveness of the implementation are legal, law enforcement, facilities, community, and cultural factors.Keywords: Implementation; Policy; Street vendors.